Search -x-y-z-x-y-z

x y z x y z

 
 

Top Questions

1. Proof by cases: Let x and y be two integers that are divisible by 4, and z be an ...

t divisible by 4. Then the sum of x, y, and z cannot be divisible by 4.
View More

4.You need to order sheet metal in order to build the above mail box. The inside will be completely empty. x ...

pty. x = 18.4 y = 9 z = 5.2 How much sheet metal would be needed to create this mail box. Round your answer to the nearest hundredth. (Example: 0.01) DO NOT label your answer with units. (Example: inches, cm, in squared)
View More

5.A recent transportation survey of w urban commuters (that is, n(U) = w) yielded the following information: x commuters rode ...

formation: x commuters rode neither trains nor buses, y rode trains, and z rode only trains. How many people rode the following? (a) trains and buses (b) only buses (c) buses (d) trains or buses I answered a easily but can't figure out b-d
View More

6.hello can you please help to solve this system of equations k == (Sqrt[y^2 - 2 y^3 - y^4 + ...

+ Sqrt[2 - 2 y] - k)/((y + 1) Sqrt[1 - y^2]), Sqrt[2]/2/m == k/(k - Sqrt[2 - 2 y]), n == Sqrt[2 - 2 Sqrt[1 - m^2]], z == Sqrt[2 - 2 y]/f == Sqrt[(zn)^2 - 2 + 2 y]/ Sqrt[n^2 - f^2], t == (Sqrt[g^2 - 2 g^3 - g^4 + 2 g + 1] + Sqrt[2 - 2 g] - t)/((g + 1) Sqrt[1 - g^2]), Sqrt[2]/2/h == t/(t - Sqrt[2 - 2 g]), q == Sqrt[2 - 2 Sqrt[1 - h^2]], l == Sqrt[2 - 2 g]/p == Sqrt[(lq)^2 - 2 + 2 g]/ Sqrt[q^2 - p^2], (z + 1) x == (l + 1) 2 x == (y + 1) Sqrt[1 - y^2]/ Sqrt[2] == Pi/4, q == m and determine true it or false thank you
View More

8.I am wondering if we have a circle and someone goes around the circle three times. 1. the first time ...

me he goes around the circle X m/s 2. the second time he goes around the circle Y m/s 3. His average velocity is Z m/s 4. What is the velocity the third time.
View More

1.AU MAT 120 Systems of Linear Equations and Inequalities Discussion

mathematicsalgebra Physics